Investigation of the Flow Field Characteristics of Aortic Bileaflet Mechanical Heart Valves with Different Leaflet Shapes Using PIV - Y. Qiang; T. C. Duan; M. Z. Zhang; L. Qi; L. J. Wei (Journal of Applied Fluid Mechanics)
Non-physiological flow patterns generated by bileaflet mechanical aortic valves are closely associated with thromboembolism following valve replacement surgery. Investigating how different leaflet shapes affect the flow field characteristics of these valves can help optimize leaflet designs to improve hemodynamic performance and reduce postoperative complications. This study used clinical CT imaging data to create a realistic silicone model of the aortic root, setting up an extracorporeal pulsatile flow system to simulate cyclical blood flow. Particle image velocimetry was used to capture the periodic flow field downstream of bileaflet mechanical aortic valves with straight and curved leaflets, analyzing the impact of leaflet shape on velocity distribution, vortex dynamics, viscous shear stress (VSS), and Reynolds shear stress (RSS). Results indicate that the curved leaflets reduced the impact on the aortic sinus, mitigating endothelial cell damage caused by high velocity. The curved leaflet design also increased the effective flow area, preventing blood stagnation and reducing local concentrations of coagulation factors, thus lowering the risk of thrombus formation. The maximum VSS for the straight and curved leaflets were 1.93 N/m2 and 1.87 N/m2, respectively, while the RSS reached 152 N/m2 and 118 N/m2, respectively. Curved leaflets minimized turbulent shear stress on blood cells, reducing platelet activation and lowering the incidence of thromboembolism. Optimizing leaflet curvature offers a promising avenue for enhancing the hemodynamic performance of bileaflet mechanical aortic valves. Curved designs may also be more suitable for older patients or those with reduced cardiac ejection capacity, improving surgical outcomes and recovery.